PENGARUH HARGA DAN KUALITAS MAKANAN TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA DI KANTIN FT UNIVERSITAS NEGERI PADANG - Safli, Asrofil Anas; Kasmita, Kasmita; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of research is to see how big influence of the price (x1) andquality of the food (x2) to the purchase decisions of the students in the cafeteria FTUNP. The sample of the in this research were 100 people taken using thetechnique of sampling purposive. The data collection was done with thequestionare using scale likert that they are highly capable validity an reability.The research result indicates that:(1)The price of food in the cafeteria FT UNPbelongs in the category of less well with values percentage 50%. (2) The qualityof the food in the cafeteria FT UNP pertained less well with values percentage of53%.(3) The purchasing decision in the cafeteria FT UNP belongs in the categoryof good with values percentage 63%.(4) The prices and food quality togetherpositive and significant effect against the purchasing decision of the student in thecafeteria FT UNP, indicated by the significant value (0.00 < 0.05) and influentialcontribution amounting to 30.9%, while the rest of the other variable specified isnot examined.Keywords: Price, Food Quality, Purchase Decision